The Impact of Power Distance Orientation on Recipients' Reactions to Participatory Versus Programmatic Change Communication. (March 2016) - Helpap, Sevda
Research has shown that managerial communication can facilitate employees' support for organizational change; however, the reasons for variations in employees' evaluations of change communication have yet to be investigated. This study examines how participatory and programmatic change communications influence the change commitment and resistance intention of recipients while taking into consideration their power distance orientation (PD orientation). We conducted an experimental simulation study with 263 German employees, mostly of lower hierarchical status. The findings reveal that participatory communication is more likely to lead to change commitment than programmatic communication, particularly for employees with low PD orientation. Employees were more likely to commit to the change vision when the leader's communication approach met the employees' expectations regarding their PD orientation, suggesting that there is a moderating effect. In addition, a moderated mediation analysis revealed that PD orientation has an indirect impact on employees' resistance intention through their level of change commitment.